[RETRACTED] Motives for Using Tik Tok in Uses and Gratification Theory Perspective: This article was retracted due to ethical misconduct, indicating double publication. - Ahmad Khairul Nuzuli (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
This article was retracted due to ethical misconduct, indicating double publication.